2016
DOI: 10.1183/16000617.0016-2016
|View full text |Cite
|
Sign up to set email alerts
|

What type of clinical evidence is needed to assess medical devices?

Abstract: The objective of this mini-review is to discuss the role of real-world studies as a source of clinical evidence when experimental studies, such as randomised controlled trials (RCTs), are not available. Waiting for RCT evidence when the technology is diffusing could be anti-economical, inefficient from the policy perspective and methodologically questionable.We explain how real-world studies could provide relevant evidence to decision makers. Matching techniques are discussed as a viable solution for bias redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
31
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 30 publications
0
31
0
Order By: Relevance
“…Two equally valid viewpoints are put forward: one is presented in a Health and Politics Mini-Review by Rosanna Tarricone [3], an economist and the Director of CERGAS, the healthcare research centre at Milan's famous Bocconi University in Italy, while the other is presented in an accompanying editorial [4] by Maria Frigerio, an extensively experienced clinical cardiologist who is the Director of the Heart Transplant and Heart Failure Programme at the De Gasperis Cardiology Centre, Milan, one of the Europe's leading cardiological and heart surgery facilities.…”
Section: @Erspublicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two equally valid viewpoints are put forward: one is presented in a Health and Politics Mini-Review by Rosanna Tarricone [3], an economist and the Director of CERGAS, the healthcare research centre at Milan's famous Bocconi University in Italy, while the other is presented in an accompanying editorial [4] by Maria Frigerio, an extensively experienced clinical cardiologist who is the Director of the Heart Transplant and Heart Failure Programme at the De Gasperis Cardiology Centre, Milan, one of the Europe's leading cardiological and heart surgery facilities.…”
Section: @Erspublicationsmentioning
confidence: 99%
“…The mini-review by TARRICONE et al [3] offers an interesting perspective on how "real world" data can be used for building reliable evidence (and, consequently, performing health technology assessments) in device-based therapies, when evidence from comparative, randomised studies are unavailable, difficult to obtain or inconclusive. This analysis, based on the example of the MitraClip device (Abbott Vascular, Santa Clara, CA, USA), leaves some significant unanswered questions: is a new technology good just because one regulator allowed it to be used, while another did not?…”
Section: @Erspublicationsmentioning
confidence: 99%
“…A point in favour of prompt commercialisation of innovative devices is that pre-market conduct of large clinical trials could be unsustainable for many enterprises: while large pharmaceutical companies may develop new molecules utilising the revenues of already approved drugs, new devices are not infrequently invented and initially developed by small/medium enterprises, focused on that single project, which is time consuming and resource demanding [3]. As a consequence, most clinical studies on new device-based therapies are performed after their commercialisation [4].…”
mentioning
confidence: 99%
“…Applying the EBM principles, if the positive findings of initial studies would not be confirmed by randomised clinical trials (RCTs), the effectiveness of the new device should be considered, at best, questionable. Conversely, doubts have been raised on the appropriateness and reliability of RCTs for evaluating medical devices [2,3]. First, most of the times these studies are unblinded for both the medical staff and the patient; patient blinding would imply "sham" procedures, which may be considered unethical in several settings.…”
mentioning
confidence: 99%
See 1 more Smart Citation